Determinants of Firm Value in Indonesia’s Coal Industry: ESG, Capital Structure, Commodity Prices - Elman Junizar Rusdi; Pardomuan Sihombing (ARE Publisher, 2026)
Objectives: This study aims to examine the effect of Environmental, Social, and Governance (ESG) disclosure, capital structure, and coal commodity prices on firm value in coal mining companies listed on the Indonesia Stock Exchange during the 2022–2024 period. Methodology: The research employs a quantitative approach with a causal design using panel data from 19 companies and 57 observations. The data are analyzed through panel data regression using the Random Effect Model. Findings: The results indicate that ESG disclosure and coal commodity prices do not have a significant effect on firm value, whereas capital structure shows a positive and significant influence. These findings suggest that the market responds more strongly to internal financing policies than to sustainability information or external commodity price fluctuations. Conclusion: The study concludes that optimizing capital structure is a primary factor in enhancing firm value, while ESG implementation needs to be aligned with financial performance to gain stronger market recognition.